RECIST 1.1 – Standardisation and disease-specific adaptations: Perspectives from the RECIST Working Group. (July 2016) - Schwartz, Lawrence H.; Seymour, Lesley; Litière, Saskia; Ford, Robert; Gwyther, Stephen; Mandrekar, Sumithra; Shankar, Lalitha; Bogaerts, Jan; Chen, Alice; Dancey, Janet; Hayes, Wendy; Hodi, F. Stephen; et al.
Abstract: Radiologic imaging of disease sites plays a pivotal role in the management of patients with cancer. Response Evaluation Criteria in Solid Tumours (RECIST), introduced in 2000, and modified in 2009, has become the de facto standard for assessment of response in solid tumours in patients on clinical trials. The RECIST Working Group considers the ability of the global oncology community to implement and adopt updates to RECIST in a timely manner to be critical. Updates to RECIST must be tested, validated and implemented in a standardised, methodical manner in response to therapeutic and imaging technology advances as well as experience gained by users. This was the case with the development of RECIST 1.1, where an expanded data warehouse was developed to test and validate modifications. Similar initiatives are ongoing, testing RECIST in the evaluation of response to non-cytotoxic agents, immunotherapies, as well as in specific diseases. The RECIST Working Group has previously outlined the level of evidence considered necessary to formally and fully validate new imaging markers as an appropriate end-point for clinical trials. Achieving the optimal level of evidence desired is a difficult feat for phase III trials; this involves a meta-analysis of multiple prospective, randomised multicentre clinical trials. The rationale for modifications should also be considered; the modifications may be proposed to improve surrogacy, to provide a more mechanistic imaging technique, or be designed to improve reproducibility of the imaging biomarker. Here, we present the commonly described modifications of RECIST, each of which is associated with different levels of evidence and validation. Highlights: The level of evidence validate a new imaging biomarker as an end-point for a specific disease or in phase II trials is considerable. This manuscript provides an overview of commonly described modifications of Response Evaluation Criteria in Solid Tumours (RECIST) with level of evidence using Oxford Centre for Evidence-Based Medicine approach. RECIST Working Group supports the evaluation and validation of novel biomarkers in cancer therapy and will work to incorporate into RECIST as the techniques and therapeutics become widely used and globally available.